(3efgGL GdHjGf ajeG jSJYedg GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi XgQJ HOGFY eUfhYGJg eSJbUQ Pdc Yf NOeI NRGFf SjOfG hehdGfG GdEeGe hdeG CfYe HbHhd GdcJGH SejJg HJbhje GdCHOGf HGOQJ HJQJjH cJGH KGf , hSejJg efgGL GdHjGf ajeG jSJYedI GdEfSGf s
(3BNQgG (B:s
(3Ci UeZ GdSPGH GdLHdi , hgh MGQ jGHS , jSgd GdHdZe hbO CSJhai PcQg hTQMg HGH GdKGA Je cJGH efgGL GdHjGf s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B259 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B275 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMji HGTG GdLdjdi (B_ (3GdehUd (B(258) s
Keywords: (3GdWHs